Peculiarities of collecting and distributing of remuneration for reproduction and private copying in Ukraine and EU countries - Kostiv, Oleksandr (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article deals with the procedure for collecting and distributing remuneration by the organizations for reproduction of works and their private copying. The author analyzes the new Law of Ukraine "On Effective Management of Property Rights of Legal Owners in the Sphere of Copyright and (or) Related Rights", which came into force on 22.08.2018 during the period of active reform of the state system of legal protection of intellectual property. The article highlights the innovations that have taken place thanks to the adoption of the Law on Effective Governance. Thus, the collected revenue from the rights of the collective management organization after deduction of the management fee is subject to distribution in proportions: 25 percent of the income from the rights collected by the accredited organization for reproduction of works are directed to the development of Ukrainian culture; the rest (75%) is distributed to the following categories of right holders in the respective parts: to authors of works of science, fiction - 50 percent; to authors of fine, photographic and other similar works - 10 percent; to publishers - 40 percent. Analyzing the mentioned rule, the author criticizes the position of the legislator, because it turns out that the restriction of property rights of the owners is the norm of the common law, while the special law "On Copyright and Related Rights" does not contain such restriction. In addition, the author insists on the lack of a clear legal status of funds that could be transferred to the development of Ukrainian culture. From the draft resolution of the Cabinet of Ministers of Ukraine "On approval of the procedure and terms of transfer by the organizations of the collective management of the shares of the rights from the state institution, which performs special functions to promote national and cultural development of Ukraine", which was prepared by the previous government, it is seen that the state institution that will perform special functions for promoting national and cultural development of Ukraine are the Ukrainian Cultural Fund. That is, it should receive funds that are recognized as "the amount of unsolicited remuneration" and the above 25% of the rights. According to the founding documents, the Ukrainian Cultural Fund is a budgetary institution which property belongs to it under the rules of economic law and the right of operational management. Author’s main questions are: How can the private funds of the right holders be forcibly transferred to a public institution? Is it about nationalization? The author sees no other answer. The latter can only be applied from the standpoint of protecting the economic security of our country. Therefore, the rate of transfer of 25% of the rights is subject to crushing criticism by the author. In the research, the author also shows the opinion of the manufacturers of the equipment which can be used for reproduction of the works and in this connection the author indicates the necessity of revising the list of such equipment. This will balance the rights of equipment manufacturers and owners’ rights. The experience of foreign countries on this issue is thoroughly explored and proposals for harmonizatio.